OBESITY AS A PRESSING MEDICAL AND SOCIAL PROBLEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Obesity is one of the most common chronic diseases of our time and represents a serious medical and social problem. It is associated with excessive accumulation of adipose tissue in the body and leads to the development of many comorbidities, including type 2 diabetes mellitus, cardiovascular pathologies, musculoskeletal system diseases, and a decrease in the quality of life. This article examines the main causes, mechanisms of development, classification, clinical manifestations, methods of diagnosis, treatment, and prevention of obesity.